TAMI-29. MR SPECTROSCOPY MEASURES OF LAC/NAA AND NAA/CHO DIFFERENTIATE SURVIVORSHIP IN PATIENTS WITH RECURRENT GLIOBLASTOMA TREATED WITH ANTI-ANGIOGENIC THERAPY. (12th November 2021) - Talati, Pratik; El-Abtah, Mohamed; Kim, Daniel; Dietrich, Jorg; Fu, Melanie; Wenke, Michael; He, Julian; Natheir, Sharif; Vangel, Mark; Rapalino, Otto; Vaynrub, Anna; Arrillaga-Romany, Isabel; et al.
Abstract: Patients with recurrent glioblastoma (rGBM) are often started on anti-angiogenic therapy such as bevacizumab. However, determining treatment failure using conventional MRI methods remains challenging. We prospectively collected longitudinal MR spectroscopy data in 33 patients with rGBM and quantified various metabolites including N-acetylaspartate (NAA), Choline (Cho), and Lactate (Lac). After stratifying patients by 9 month survival, we found that longer-term survivors had decreased Lac/NAA and increased NAA/Cho compared to shorter-term survivors. ROC analyses illustrated that intratumoral changes in NAA/Cho were predictive of survival at 1 day (AUC 0.92), 2 weeks (AUC 0.75), 8 weeks (AUC 0.71) and 16 weeks (AUC 0.85) but not 4 weeks (AUC 0.60). Intratumoral changes in Lac/NAA were predictive of survival at all time points tested (AUCs > 0.76 for all time points). At 8 weeks, 90% of patients with increased Lac/NAA from baseline and 88% of patients with decreased NAA/Cho did not survive 9 months. Changes in NAA/Cho and Lac/NAA may serve as early biomarkers of anti-angiogenic treatment failure.